2007
DOI: 10.1074/jbc.m602931200
|View full text |Cite
|
Sign up to set email alerts
|

An Active Nuclear Retention Signal in the Glucocorticoid Receptor Functions as a Strong Inducer of Transcriptional Activation

Abstract: The glucocorticoid receptor (GR) cycles between a naive chaperone-complexed form in the cytoplasm and a transcriptionally active steroid-bound nuclear form. Nuclear import of GR occurs rapidly and is mediated through the importin ␣/␤ karyopherin import pathway. By contrast, nuclear export of GR occurs only slowly under most conditions, despite a dependence on active signaling. In this study we have defined a nuclear retention signal (NRS) in the hinge region of GR that actively opposes the nuclear export of GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…The H2 ER␣ mutant must be counteracted by a nuclear export signal to keep the nucleocentric ER␣ out of the nucleus. The glucocorticoid receptor (GR) has a nuclear retention signal that overlaps the nuclear localization function and is necessary for ligand bound transcriptional activation (41). A similar nuclear retention signal or event for ER␣ is possible and the cytoplasmic versus nuclear distribution of the H1 and H2 ER␣ mutants suggest that this region of ER␣ may be responsible for ligand-dependent nuclear retention of ER␣.…”
Section: Discussionmentioning
confidence: 99%
“…The H2 ER␣ mutant must be counteracted by a nuclear export signal to keep the nucleocentric ER␣ out of the nucleus. The glucocorticoid receptor (GR) has a nuclear retention signal that overlaps the nuclear localization function and is necessary for ligand bound transcriptional activation (41). A similar nuclear retention signal or event for ER␣ is possible and the cytoplasmic versus nuclear distribution of the H1 and H2 ER␣ mutants suggest that this region of ER␣ may be responsible for ligand-dependent nuclear retention of ER␣.…”
Section: Discussionmentioning
confidence: 99%
“…Human GR hinge region DNA-PK phosphorylation site Ser-508 implicated in GR nuclear retention (63,66,67) is positioned close to human GR nuclear targeting residues 479 -498 and is displaced in position by two residues to the corresponding human AR hinge residue Ser-650 near AR nuclear targeting residues 617-633 (22,68). We and others have shown that a mutation at Ser-650 has relatively little effect on AR transcriptional activity (28,35).…”
Section: Discussionmentioning
confidence: 99%
“…Within this context the decrease in maximal nuclear import and increase in nuclear export rate for CpdA-bound wtGR, as for Dex-bound GR dim , as compared with Dex-bound wtGR, shown in the current paper, suggests that loss of GR dimerization results in a GR species that exits the nucleus at a significantly faster rate and that GR dimerization contributes to the amount of GR present in the nucleus upon ligand activation. Previous work has suggested that the hinge region of the GR contains a solution dimerization domain (23) involved in cytosolic dimerization of the liganded GR, a nuclear localization signal, NL1 (40), that mediates liganded and unliganded GR nuclear location, and a nuclear retention signal that actively retains the GR in the nucleus (67). Loss of NL1 and nuclear retention signal results in increased nuclear export and reduced nuclear occupancy, which closely resembles the effect found with CpdA and GR dim in the current study.…”
Section: Discussionmentioning
confidence: 99%